2012
DOI: 10.1590/s1517-83822012000200034
|View full text |Cite
|
Sign up to set email alerts
|

Association of TLR4 polymorphisms with subclinical mastitis in Brazilian holsteins

Abstract: The identification of dairy cows with greater or lower potential to develop mastits has been pursued for many years among different segments of the milk industry, including governmental organizations. Genomic studies have suggested that Single Nucleotide Polymorphisms (SNPs) within the pattern recognition receptors (PRR) could lead to different responses to pathogens, and consequently result in mastitis resistance or susceptibility. To investigate whether toll like receptor 4 (TLR4) gene is associated with sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…There was a nonsynonymous mutation in exon 3 (SNP 9787C>T) which had changed amino acid tyrosine to lysine. All these SNPs were reported earlier (seven SNPs by Wang et al 9 one SNP by Mesquita et al ) 10 There was no novel SNP found in TLR4 gene in the present study. The SNPs and other variations found in the nucleotide sequences of expressed regions of bovine TLR4 gene among the crossbred populations are presented in Table 1.…”
Section: Nucleotide Sequence Of Bovine Tlr4 Genesupporting
confidence: 72%
See 1 more Smart Citation
“…There was a nonsynonymous mutation in exon 3 (SNP 9787C>T) which had changed amino acid tyrosine to lysine. All these SNPs were reported earlier (seven SNPs by Wang et al 9 one SNP by Mesquita et al ) 10 There was no novel SNP found in TLR4 gene in the present study. The SNPs and other variations found in the nucleotide sequences of expressed regions of bovine TLR4 gene among the crossbred populations are presented in Table 1.…”
Section: Nucleotide Sequence Of Bovine Tlr4 Genesupporting
confidence: 72%
“…Similarly, no association was found between TLR4 gene SNP 245G>C and SCS in earlier studies also. 5,11 On the contrary, associations were found between SNP 245 and SNP 5087 and SCS 10 and between SNP 9787 and SCS. 9…”
Section: Association Of Tlr4 Gene With Scsmentioning
confidence: 88%
“…According to Sender et al (2013) the best cumulative genotype does not identify individual genes, and animals are selected based on the estimated cumulative impact of multiple genes on resistance to mastitis. Mesquita et al (2012) studied Brazilian Holsteins for TLR4 polymorphism indicated that animals with combined genotypes AACCCC, GGTCGG, and GACCGC presented the lowest SCS and have the potential to be applied as molecular markers for assisted animal selection to improve milk quality. Six combined genotypes of two TLR4 gene SNPs (c.9421C>T and c.2021C>T) were observed, though only one cow had a CC/TC and CC/TT combined genotype.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining variants identified all represented synonymous variations. TLR4 region analyzed for somatic cell score (SCS) and 3 SNPs were associated with high and low SCS values (intron1 rs8193046 A/G, exon3 rs8193060 C/T, 5'UTR rs29017188 C/G) [52]. ACC haplotype was associated with low SCS whereas GTG haplotype was associated with high SCS.…”
Section: Discussionmentioning
confidence: 99%